2022
DOI: 10.1177/21925682221081030
|View full text |Cite
|
Sign up to set email alerts
|

Reoperations After Percutaneous Endoscopic Transforaminal Decompression for Treating Lumbar Spinal Stenosis: Incidence and Predictors

Abstract: Study Design Retrospective cohort study. Objectives The main purpose of the present study was to report the incidence and identify predictors of reoperation in patients with lumbar spinal stenosis (LSS) treated with percutaneous endoscopic transforaminal decompression (PETD). Methods This study retrospectively reviewed consecutive patients with LSS who underwent PETD at our center between January 2016 and July 2020. The incidence of reoperations was calculated. We then designed a surgical period-matched case-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Yin (7) concluded that age and BMI could influence recurrence rate. Our previous study also confirmed that age was a risk factor for reoperation after PTED (19). However, we found that the associations between age, sex, and reoperation were ambiguous in the existing literature.…”
Section: Discussionsupporting
confidence: 79%
“…Yin (7) concluded that age and BMI could influence recurrence rate. Our previous study also confirmed that age was a risk factor for reoperation after PTED (19). However, we found that the associations between age, sex, and reoperation were ambiguous in the existing literature.…”
Section: Discussionsupporting
confidence: 79%
“…Recurrence after LSS is a common complication, and the choice of revision method is key to improving the success rate of revision surgery. Previous studies have focused on revision rates and risk factors leading to revision; 16 , 24–26 however, studies on the efficacy of revision PELD surgery have rarely been reported. Xu et al evaluated the efficacy of reoperation after percutaneous transforaminal endoscopic discectomy for LSS.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior study found that the revision rate after PELD for LSS was 6.7%, for which the same-segment revision rate was 4.4%, and that age was a risk factor for revision. 16 However, few studies have reported the efficacy of reoperation in patients with recurrent LSS. Therefore, this study followed up patients with PELD recurrence due to LSS in our and other hospitals, and evaluated the efficacy of PELD revision surgery.…”
Section: Introductionmentioning
confidence: 99%